La costruzione sociale della finanziarizzazione: verso la convergenza dei sistemi bancari? - Betti, Marco (Premio Ricerca «Città di Firenze», 2016)
The developments in the globalization process, the increased strength of European integration and the improvements in communication technologies have put the convergence of institutional structures of the different capitalist systems at the centre of the debate. In this perspective, banks play a crucial role. In the new context, movable assets become indeed increasingly profitable, which reduces the weight of traditional activities in the financial statements of banking institutions. Starting from these premises, the volume investigates the extent of the de-intermediation and financialisation processes of the main Italian banks, deepening their connection with the cultural, relational and political dimension.